Height does not impair the hydraulic system of the tallest tropical Dipterocarp trees - Paulo Bittencourt; Arne Scheire; Palasiah Jotan; Jehova Lourenço; Lindsay F. Banin; Mohd Aminur Faiz bin Suis; David F. R. P. Burslem; Bradley Christoffersen; David Coomes; Peter Groenendijk; Steven Jansen; Tommaso Jucker; et al. (Science, 2026)
Half of the aboveground biomass in forests is stored in a disproportionately small number of very tall trees. These giants are predicted to be more vulnerable to drought-induced damage because height impairs their hydraulic system. We evaluated whether the hydraulic system of world’s tallest tropical tree species—Southeast Asian dipterocarps—are negatively affected by their height. The more negative xylem pressures caused by tree height were fully compensated for through adjustment of vessel anatomy and leaf hydraulic traits, and the trees suffered no height-related loss in growth during a severe drought. Therefore, height does not make the hydraulic systems of the world’s tallest tropical tree species more vulnerable to drought, and the growth rates of these trees are not more negatively affected by drought than are their smaller counterparts.